Wsparcie finansowe sektora małych i średnich przedsiębiorstw - wybrane inicjatywy i instrumenty Unii Europejskiej - Wojtasiak, Agnieszka (Financial support for small and medium enterprises - selected initiatives and instruments of the European Union, 2006)
SMEs today play a central role in the European Union (EU) economy. One of the European Union’s aims is to promote successful entrepreneurship and to improve the business environment for SMEs, to allow them to meet the challenges faced in today’s economy to realize their full potential This paper covers financial instruments managed by the EIF in the name of the EC. Main goal of these instruments is to increase SMEs access to loans, guarantees and equity financing. The budgetary and legal framework for these instruments are Multiannual programme for enterprise and entrepreneurship, and in particular for small and medium-sized enterprises. The successor of this program will be Competitiveness and Innovation Programme.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 575-583